Bring your own device (BYOD) to work : trend report - Hayes, Bob E., 1963- (Security Executive Council risk management portfolio., 2013)
Bring Your Own Device (BYOD) to Work examines the emerging BYOD (Bring Your Own Device to work) trend in corporate IT. BYOD is the practice of employees bringing personally-owned mobile devices (e.g., smartphones, tablets, laptops) to the workplace, and using those devices to access company resources such as email, file servers, and databases. BYOD presents unique challenges in data privacy, confidentiality, security, productivity, and acceptable use that must be met proactively by information security professionals. This report provides solid background on the practice, original research on its pros and cons, and actionable recommendations for implementing a BYOD program. Successful programs are cross-functional efforts including information technology, human resources, finance, legal, security, and business operating teams. This report is a valuable resource to any security professional considering a BYOD program. Presents research data associated with BYOD and productivity in the workplace. Describes BYOD challenges, risks, and liabilities. Makes recommendations for the components a clearly communicated BYOD program should contain.